2002
DOI: 10.1289/ehp.02110s4573
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic evidence for asthma and exposure to air toxics: linkages between occupational, indoor, and community air pollution research.

Abstract: Outdoor ambient air pollutant exposures in communities are relevant to the acute exacerbation and possibly the onset of asthma. However, the complexity of pollutant mixtures and etiologic heterogeneity of asthma has made it difficult to identify causal components in those mixtures. Occupational exposures associated with asthma may yield clues to causal components in ambient air pollution because such exposures are often identifiable as single-chemical agents (e.g., metal compounds). However, translating occupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
158
1
6

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(169 citation statements)
references
References 144 publications
4
158
1
6
Order By: Relevance
“…Epidemiological studies indicate a relationship between exposure to formaldehyde and clinical manifestation of asthma and sensitization to common allergens [4,[30][31][32][33]. Our results did not reveal significant differences between the investigated groups in terms of history of symptoms and suspected or diagnosed allergic diseases.…”
Section: Discussioncontrasting
confidence: 59%
“…Epidemiological studies indicate a relationship between exposure to formaldehyde and clinical manifestation of asthma and sensitization to common allergens [4,[30][31][32][33]. Our results did not reveal significant differences between the investigated groups in terms of history of symptoms and suspected or diagnosed allergic diseases.…”
Section: Discussioncontrasting
confidence: 59%
“…Volatile organic compounds (VOCS) have also been suspected to be associated with other noncancer health effects, such as asthma, although these associations remain largely unproven (12). Despite these potentially harmful human health impacts, there are relatively few studies that quantify exposure to VOCs and aldehydes in diesel-heavy and other vehicle exhaust-related microenvironments (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations of PM 10 and PM 2.5 are proportional to the quantity of dust, which is a result of outdoor air entering through the ventilation system and due to the movement of passengers. Recent studies (Delfino, 2002;Ormstad, 2000) on PMs of indoor showed that they contain large amounts of potential allergy carriers, and they could cause respiratory illness such as asthma. Especially, PM 2.5 can lodge deeply into the lungs because of their small size.…”
Section: Analysis Of Hourly Iaq Datamentioning
confidence: 99%